Post-transcriptional control in Escherichia coli: translation and degradation of the atp operon mRNA - McCarthy, John E.G.; Schauder, Birgit; Ziemke, Peter (Gene, 1988)
An attractive subject for investigations of post-transcriptional control is the atp operon, whose nine genes are differentially expressed. The primary mode of control of atp gene expression is exercised at the translational level. It has been clearly demonstrated for almost all of the atp genes that the primary and secondary structures of their respective translational initiation regions direct translational initiation rates that correspond well to the requirements for these subunits in the cell. The relationship between the structure of the translational initiation region, including bases upstream from the Shine-Dalgamo region and downstream from the start codon, and the rates of initiation that it determines, has been investigated in more detail using various polycistronic and monocistronic systems. No evidence could be found for a role of codon usage bias in controlling overall translation rates. The functional half-lives of atpE and of the other six cistrons downstream from it are similar. The chemical stabilities of the first two cistrons of the polycistronic atp mRNA may, however, be lower, and we are investigating the possibility that there may also be control of atp gene expression exercised at the level of mRNA stability. The effects of manipulations of the intercistronic regions of at least the plasmid borne atp operon are consistent with a model of mRNA decay in which rate control is associated with endonucleolytic cleavages within individual cistrons. The experimental data are discussed in relation to the possible ways in which primary and secondary structures of the mRNA might control translational efficiency and stability.